K razvitiyu obshchei teorii sportivnoi podgotovki - Kulikov, L. M.; Rybakov, V. V. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The article is dedicated to the problem of the general theory of sports training development. The authors offer three levels of that problem's study: the system approach, the accuracy and reliability of the research, the using of the equal methods of investigation. They represent the materials on the assigned loads and the adaptational responses to them and, they profound the thesis about the optimal order and duration of the various predominantly aimed loads in a training process's structures.